2009
DOI: 10.2322/tstj.7.pr_2_7
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for Active Debris Removal Using Electrodynamic Tether

Abstract: In this study, the active removal of space debris is studied from the point of view of technological feasibility. First, the actual debris distribution is analyzed to determine which debris objects should be removed considering the effectiveness in preventing collisional cascading and feasibility such as the delta-V required for rendezvous with the objects. Target regions such as sun-synchronous orbit and a 1,000km altitude, 83 degree inclination orbit are then selected and rendezvous with debris object in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…In order to protect the man-made space assets against these threats caused by the orbital debris, many orbital debris clearing systems have been proposed [4][5][6][7][8][9][10], such as the ROGER System [4][5], the Space Tether Net System [6][7] and the pulsed laser orbital debris removal (LODR)concept [8][9]. The ROGER System is proposed by EADS in 2003, which introduced two different mechanisms, including a gripper and a net, to capture the malfunction satellites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to protect the man-made space assets against these threats caused by the orbital debris, many orbital debris clearing systems have been proposed [4][5][6][7][8][9][10], such as the ROGER System [4][5], the Space Tether Net System [6][7] and the pulsed laser orbital debris removal (LODR)concept [8][9]. The ROGER System is proposed by EADS in 2003, which introduced two different mechanisms, including a gripper and a net, to capture the malfunction satellites.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the imaginable Manuscript received July 31, 2013. This work was supported by the National Natural Science Foundation of China (Grant No: 11272256) approach of removing the larger orbital debris by electrodynamics tethers is also discussed in reference [10]. However, the above orbital debris clearing systems still have several challenges during their clearing missions.…”
Section: Introductionmentioning
confidence: 99%
“…From this perspective, electrodynamic tether (EDT) systems are very promising since they can generate sufficient thrust for orbital transfers without the need for propellant by utilizing interactions with Earth's magnetic field. Previous studies have shown that an EDT could deorbit many large debris items from the crowded orbits within one year 3,4) . Furthermore, the thrust of the EDT is so low that it does not have to be as firmly attached to the target as a conventional propulsion system, so attaching it to a debris object by a robot arm will be less challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The orbits of debris objects are observed by the ground radars and optical telescopes of the North American Aerospace Defense Command (NORAD), and their orbital elements are published. It is found that many debris objects exist in some specific crowded regions such as Sun-Synchronous Orbit (SSO), 900-1,000 km altitude and 83 inclination, and 1,400-1,500 km altitude and 74, 83, or 52 inclinations 7) . Within these regions several debris objects can be found within an inclination difference of less than 1 and a RAAN (right accession of ascending node) difference of less than a few degrees, so it will be feasible for a single removal satellite to remove several objects.…”
Section: Target Of Removalmentioning
confidence: 99%